Application of servant leadership dimension of village head to improve the performance of Village Apparatus in Kerinci Regency - Sudirman Sudirman; Maryanto Maryanto; Ayu Esteka Sari (Trigin Publisher, 2023)
The purpose of this study is to analyze how the application of the servant leadership dimension of the village head improves the performance of the village apparatus in Kerinci Regency. Novelty in this study: to develop and formulate a model of the dimension of servant leadership of village heads to improve the performance of village apparatus. The research was conducted in Kerinci District, Jambi Province. This study used quantitative research methods. To obtain valid data and information, researchers use interviews, observation, surveys, and documentation techniques. Model Testing Techniques using Structural Equation Model (SEM) with AMOS. The population is the entire village apparatus in Kerinci Regency. The sampling technique is an accidental sampling method, with the number of samples representing the population with a total of 103 responses. For the Servant leadership equation of 0,998 which means the factors that affect the variability of Servant leadership can be explained by the variables Altruistic calling, Emotional healing, Wisdom, Persuasive mapping, Organizational stewardship, Humility, Vision, and Service of 99,8%. The coefficient of determination of the Village Apparatus Performance equation is 0,972 or the Village Apparatus Performance variable which can be explained by the variability of Servant leadership of 97,2%.